Advances in gene therapy and their application to skin diseases: A review. Issue 1 (July 2021) - Shinkuma, Satoru
Highlights: Gene therapy represents a viable treatment option for various diseases. Clinical trials have been conducted on gene therapy addressing genodermatoses. This review summarizes the current use of gene therapy in the dermatological field. Superficial gene-therapy sites can be evaluated for presence of neoplasms. Therefore, dermatologists have an important role in gene therapy application. Abstract: With recent advances in genetic engineering technology, gene therapy is now being considered as a treatment not only for congenital diseases but also acquired diseases, such as cancer. Gene therapeutic agents for hereditary immune disorders, haemophilia, retinal diseases, neurodegenerative diseases, and lymphoma have been approved in the United States and Europe. In the field of dermatology, clinical trials of gene therapy have been conducted, because the skin is an easily accessible organ that represents an attractive tissue for gene therapy. In recent years, gene therapy has been attempted for a variety of skin diseases, such as genodermatoses (including epidermolysis bullosa and Netherton syndrome), cutaneous lymphoma, and malignant melanoma. As a result, it is difficult to grasp the current status of gene therapy in dermatology. This review focuses on each of the gene-transfer techniques currently in use and describes the current status of gene therapy for skin diseases using each technology.